SOPHIA an interactive cluster-based retrieval system for the OHSUMED collection. - Dobrynin, V.
The ability to perform an exploratory search and retrieval of relevant documents from a large collection of domain-specific documents is an important requirement both in the field of medicine and other areas. In this paper, we present a unsupervised distributional clustering technique called SOPHIA. SOPHIA provides a semantically meaningful visual clustering of the document corpus in conjunction with an intuitive interactive search facility. We assess the effectiveness of SOPHIA's cluster-based information retrieval for the MEDLINE testset collection known as OHSUMED.
Keywords: MEDLINE testset collection; OHSUMED collection; SOPHIA; Cluster-based information retrieval; Document corpus; Domain-specific document; Exploratory search; Interactive cluster-based retrieval system; Interactive search faculty; Semantically meaningful visual clustering; Unsupervised distributional clustering technique